2019
DOI: 10.1159/000503139
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Toxocara</i></b> Optic Disc Granuloma: Deep Range Imaging Optical Coherence Tomography Findings

Abstract: We aimed to present a unique case of a child with an optic disc granuloma with exudative retinal detachment as a manifestation of ocular toxocariasis. The response to systemic therapy was assessed using deep range imaging optical coherence tomography. This imaging technique was the most accurate for identification of retinal, macular and vitreous changes associated with this intraocular pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The ability to visualize signals in the retrobulbar tissue beyond the sclera is known to be dependent on the wavelength used by the OCT technology [13,[17][18][19][20]. In this study, no differences were observed in the group of control eyes where the choroidal thickness is expected to be thicker compared to myopic eyes, which may reduce the chance to image even deeper structures.…”
Section: Discussionmentioning
confidence: 67%
“…The ability to visualize signals in the retrobulbar tissue beyond the sclera is known to be dependent on the wavelength used by the OCT technology [13,[17][18][19][20]. In this study, no differences were observed in the group of control eyes where the choroidal thickness is expected to be thicker compared to myopic eyes, which may reduce the chance to image even deeper structures.…”
Section: Discussionmentioning
confidence: 67%